Pemanfaatan Limbah Serat Tembaga terhadap Nilai Kuat Tekan dan Nilai Tarik Belah Beton pada Perkerasan Kaku - Naila Amrillah; Edison Hatoguan Manurung; Dwi Purwanto (NUCLEUS, 2022)
Rigid pavement (cement concrete) is placed directly on the subgrade or foundation with or without an asphalt layer and is a pavement construction that acts as a layer for the concrete slab. One of the rigid pavements commonly used in Indonesia is rigid pavement without reinforcement which is commonly applied in residential areas and areas with low traffic frequency. However, the unreinforced pavement has a low split tensile strength which causes cracks in some of the slabs due to stress caused by traffic loads, which is why reinforcement is needed in the concrete slab to prevent the crack from extending. This study involved copper fiber from electronic cables as an alternative to concrete mixtures to prevent the elongation of cracks in the pavement slab, for this reason the researchers experimented using 8 cm fiber length and 0.8 mm fiber diameter and then twisted the fiber and the fiber variation was 1.5%. , 1%, 0.5%, and 0% of the concrete mixture and then tested when the concrete is 28 days old. The mean score of the split tensile strength of 1.5% variation is 2.273 Mpa, the mean score of the tensile strength of 1% variation is 2.284 Mpa, the mean score of the variation of 0% compressive strength is 30.740 Mpa, the mean score of 0.5% variation is 33,733 Mpa, the mean score of 0.5% tensile strength variation is 2.42 Mpa, the mean 1% variation compressive strength score is 35,035 Mpa and the mean variation compressive strength score of 1.5% is 34,760 Mpa while the mean 0% split tensile strength score is 2.057 MPa.